2017
DOI: 10.1177/0898010116684960
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perceptions of Competence in Providing Spiritual Care

Abstract: It is important for nurses to have the opportunity to gain knowledge regarding this significant component of holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
3
9
0
4
Order By: Relevance
“…The highest score on competence level was for subscale ‘ communication’, which was consistent with other studies (Abell et al, 2018; Vogel & Schep‐Akkerman, 2018). It indicated that nurses were quite confident about their communications with patients on spiritual issues.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The highest score on competence level was for subscale ‘ communication’, which was consistent with other studies (Abell et al, 2018; Vogel & Schep‐Akkerman, 2018). It indicated that nurses were quite confident about their communications with patients on spiritual issues.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the mean of total score of nurses’ spiritual care competence was 2.66 (0.73). The mean score for each dimension of spiritual care competence (mean score varying from 2.25 to 3.48) was all below 4, which indicated a need for education to improve nurses’ ability in spiritual supporting (Abell et al, 2018). Tailored training modules should be implemented to enhance the skills individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of addressing the spiritual/existential issues with patients as part of holistic care has been affirmed by an increasing amount of spirituality research (Abell et al, 2018). According to Best et al (2015a), suffering can be alleviated in cancer patients when the spiritual is addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of the present study, the nurses reported a desirable level of competence in providing spiritual care. [ 18 ] In one study conducted in 2014 in Iran, Adib-Hajbaghery et al . examined the competence of 239 nurses in providing spiritual care to patients.…”
Section: Discussionmentioning
confidence: 99%